The Influence of The Corruption Perception Index, Exports of Goods and Services, and Unemployment Rate on Economic Growth in 9 ASEAN Countries - Lusi Susanti; Muhammad Husaini (Lafadz Jaya Publisher, 2023)
This study aims to analyze the relationship between the index of corruption perceptions, exports of goods and services, and the unemployment rate on economic growth in 9 ASEAN countries. This study uses panel data from 2016-2020 in 9 ASEAN countries. The variables used are economic growth with the independent variable index of perceptions of corruption, exports of goods and services, and the unemployment rate. Based on the regression results, the corruption perception index variable has no effect on economic growth in 9 ASEAN countries. While the variable exports of goods and services have a positive and significant effect on economic growth in 9 ASEAN countries. And the unemployment rate variable has a negative and significant effect on economic growth in 9 ASEAN countries.